KEMAMPUAN PEMECAHAN MASALAH DALAM MENYELESAIKAN MASALAH ALJABAR LINEAR PADA PEMBELAJARAN DARING UNIVERSITAS BORNEO TARAKAN - Ferryansyah, Ferryansyah; Chandra, Liswiki (Mathematics Education And Application Journal (META), 2021)
AbstractThis study aims to describe problem solving abilities in solving linear algebra problems of students majoring in Mathematics Education at UBT in online learning, for each indicator of mathematical problem solving ability. The type of research used in this research is descriptive with a quantitative approach. The data collection method uses a problem-solving ability test in solving linear algebra problems in the form of descriptions. The test of mathematical problem solving ability is carried out online using the Zoom and WhatsApp applications. The sample in this study amounted to 73 students who were taken using a saturated sampling technique. The results of this study indicate that the indicator for understanding the problem is in the high category with an average value of 77.35 or with a percentage value of 35.72%, the indicator for planning completion is in the medium category with an average value of 61.73 or with a percentage value of 28.51%, the indicator carries out completion. classified in the medium category with an average value of 42.83 or with a percentage value of 19.78%, and the re-examination indicator is classified as a medium category with an average value of 34.61 or a percentage value of 15.98%.Â Keywords: Mathematical Problem Solving Ability, Online Learning.AbstrakPenelitian ini bertujuan untuk mendeskripsikan kemampuan pemecahan masalah dalam menyelesaikan masalah aljabar linear mahasiswa jurusan Pendidikan Matematika UBT pada pembelajaran daring, untuk setiap indikator kemampuan pemecahan masalah matematika. Jenis penelitian yang digunakan dalam penelitian ini adalah deskriptif dengan pendekatan kuantitatif. Metode pengumpulan data menggunakan tes kemampuan pemecahan masalah dalam menyelesaikan masalah aljabar linear berupa uraian. Adapun pemberian tes kemampuan pemecahan masalah matematika dilakukan secara daring menggunakan aplikasi Zoom dan WhatsApp. Sampel dalam penelitian ini berjumlah 73 mahasiswa yang diambil menggunakan teknik sampling jenuh. .Hasil penelitian ini menujukkan bahwa untuk indikator memahami masalah tergolong kategori tinggi dengan nilai rata-rata sebesar 77.35 atau dengan nilai persentase 35.72%, indikator merencanakan penyelesaian tergolong kategori sedang dengan nilai rata-rata sebesar 61.73 atau dengan nilai persentase 28.51%, indikator melaksanakan penyelesaian tergolong kategori sedang dengan nilai rata-rata sebesar 42.83 atau dengan nilai persentase 19.78%, dan indikator memeriksa kembali tergolong kategori sedang dengan nilai rata-rata sebesar 34.61 atau dengan nilai persentase 15.98%.Kata kunci: Kemampuan Pemecahan Masalah Matematika, Pembelajaran Daring